2023
DOI: 10.1101/2023.04.19.537548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoding Complexity in Biomolecular Recognition of Dna I-Motifs

Abstract: DNA i-motifs (iMs) are non-canonical C-rich secondary structures implicated in numerous cellular processes. Though iMs exist throughout the genome, our understanding of iM recognition by proteins or small molecules is limited to a few examples. We designed a DNA microarray containing 10,976 genomic iM sequences to examine the binding profiles of four iM-binding proteins, mitoxantrone, and the iMab antibody. iMab microarray screens demonstrated that pH 6.5, 5% BSA buffer was optimal, and fluorescence was correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 52 publications
4
5
0
Order By: Relevance
“…Using the hRAD17 model as a paradigm, we showed that iMFPS displaying occur in cells as a mix of folded (iM) and unfolded states; we showed that the populations of folded (iM) and unfolded states differed between the M and early S phases of the cell cycle. Consistent with the existing literature, 14,17,41,44 we observed that our iMFSP models introduced into cells interacted with endogenous proteins.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Using the hRAD17 model as a paradigm, we showed that iMFPS displaying occur in cells as a mix of folded (iM) and unfolded states; we showed that the populations of folded (iM) and unfolded states differed between the M and early S phases of the cell cycle. Consistent with the existing literature, 14,17,41,44 we observed that our iMFSP models introduced into cells interacted with endogenous proteins.…”
Section: Discussionsupporting
confidence: 91%
“…It is essential to emphasize that all the scenarios outlined regard that iM formation, accounting for coil-to-iM and iM-to-coil transitions in chromatin context, is a consecutive (subordinate) step to competing processes related to strand separation (i.e., duplex-to-coil/coil-to-duplex transitions) and DNA-protein binding. 17,55 Evidence suggests that the chromatin microenvironment controls the duplex-to-coil/coil-to-duplex transitions in a double-stranded chromatin context; Selvam et al 24 observed that decreasing superhelicity in torsionally constrained dsDNA fragments in an acidic solution led to duplex destabilization and an increased formation of iM, consistent with earlier findings by Hurley’s group. 23 Later, the same research team demonstrated that the DNA duplex is also significantly destabilized under confined conditions marked by reduced water activity, 25 aligning with prior observations.…”
Section: Discussionsupporting
confidence: 70%
“…Consistent with the existing literature, 14,17,43,46 we observed that our iMFSP models introduced into cells interacted with endogenous proteins.…”
Section: Notesupporting
confidence: 91%
“…To con rm the protein binding to our constructs, we performed the shift-western blot 42 (WB) analysis of PAGE-resolved lysate prepared from HeLa cells transfected with hTel and hT121-6 (Fig. S7B), using antibodies against three promiscuous and previously described DNA C-rich binding proteins 14,16,17,43 , namely hnRNP K, hnRNP A1, and PCBP2. The WB con rmed the binding of all three proteins to hTel and hT121-6 (Fig.…”
Section: Notementioning
confidence: 99%
See 1 more Smart Citation